Fabric as A Cultural Language: A Comparative Study of Symbolism in Shu Brocade and Solo Batik - Dyah Tisnawati Aulia Meylana; Clearezta Alika Yusman; Sherafina Liv Wibisono; Afin Nadhifah; Rudiansyah (Universitas Negeri Malang, 2026)
This study examines traditional textiles as a form of cultural language by analyzing the symbols contained in Shu Brocade from Sichuan, China, and Solo Batik from Indonesia. Both types of textiles represent important cultural heritage, reflecting aesthetic values, historical development, and philosophical meanings within their respective societies. This study employs a descriptive approach with content analysis based on secondary data, namely academic journals, books, and visual documentation related to both types of textiles. The findings indicate that Solo Batik reflects Javanese cultural values through motifs such as Parang, Kawung, and Sidomukti, which symbolize strength, self-control, balance, harmony, as well as hopes for prosperity and well-being. These motifs are closely intertwined with social structures, spirituality, and the philosophy of life within Javanese culture. Conversely, Shu Brocade embodies Chinese philosophical concepts through a diverse array of motifs, such as plants, animals, geometric patterns, and mythological symbols like the dragon and phoenix. These motifs symbolize auspicious meanings, such as good fortune, harmony, strength, protection, and the balance of the universe, reflecting the relationship between humans, nature, and spirituality. Although they originate from different cultural backgrounds, both woven fabrics share similarities in their intricate production techniques, symbolic motifs, aesthetic richness, and their social and cultural functions. Both also serve as a medium for conveying cultural identity and preserving these values for future generations. This study concludes that Shu Brocade and Solo Batik are not merely artistic textile products but also meaningful cultural expressions that convey values, beliefs, and identity, thus necessitating their preservation and development to remain relevant in the modern era.